The dog I loved - Wilson, Susan, 1951- (St. Martin's Press, 2019)
After spending years in prison for a crime she didn't intend to commit, Rose Collins is suddenly free. Someone who knows about the good work she has done training therapy dogs while serving time has arranged for her early release. This mysterious benefactor has even set her up with a job in the coastal Massachusetts community of Gloucester, on the edge of Dogtown, a place of legend and, for the first time since Rosie's whole world came crashing down, hope. There she works to rebuild her life with the help of Shadow, a stray dog who appears one rainy night and refuses to leave Rose's side.